Hubungan Sarapan Pagi dengan Kejadian Stunting pada Anak SD di SDN 101878 Kanan 1 Buntu Bedimbar, Tanjung Morawa - Saragih, Gloria Sepriandi; Angkat, Abdul Hairuddin (Media Gizi Ilmiah Indonesia, 2024)
Stunting is a nutritional problem that is always faced in the world. Stunting increases the risk of morbidity and death in the brain as well as delayed motor development and stunted growth in the body. Breakfast is important because it fulfills a quarter of the daily nutritional needs of school children. The aim of the research was to determine the relationship between breakfast habits and the incidence of stunting in elementary school children. The research was conducted at UPT SDN 101878 Kanan I. Observational research method with a cross-sectional design. The research population was all students in grades I-V as many as 19S5 with a sample of 78 students. Data were collected using a semi-FFQ questionnaire, amount of breakfast intake and height measurement. Statistical analysis used Chi-Square. The results of the research showed that the amount of breakfast consumption with good energy intake was 67.9% and less than 32.1%, protein intake was good at 83.3% and less than 16.7%, fat intake was good at 69.2% and less at 30.8%. Nutritional status was in the normal category 80.8%, short 16.7% and very short 2.6%. The conclusion is that there is a relationship between energy intake, protein intake, fat intake and the incidence of stunting. However, there is no relationship between breakfast habits and the incidence of stunting. The suggestion to the school is that students are expected to always go to school for breakfast every morning in order to meet a quarter of the daily needs of children at school